Proposal of a Portuguese/Kimbundu Bilingual Atlas of Human Anatomy - da Silva, Ana Pita Grós Martins (Seven Editora, 2024)
This work has as its central theme Proposal of a Portuguese/Kimbundu Bilingual Atlas of Human Anatomy. It is an interdisciplinary investigation, involving the areas of Linguistics and Medicine. The research focuses on the perspective of contributing to the promotion and diversification of theories and teaching methods articulated with the Didactics of the Teaching of Portuguese as a Second Language in the general education system, as well as on the valorization and promotion of Angolan languages. We think that the work will be very interesting, as it will contribute to the lack of information that is felt at the family and school level on issues related to the anatomy of the human body in the complete clarification of its constitution and functioning of the body, safeguarding the possible social phenomena linked to child sexual violence in our country, as well as, in the protection, diagnosis and cure of certain diseases. The bilingual study of Human Anatomy is essential for the knowledge and understanding of the human body as a whole, when the mother tongue of the students is different from the language of instruction. Thus, the interaction and immersion of the student in all the structures and characteristics of each of the organs, or parts, becomes effective as an essential means to promote life, prevent, care for and cure ailments as a technique, art and science. DOI:https://doi.org/10.56238/sevened2024.026-044